2009
DOI: 10.1111/j.1423-0410.2008.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of bead array technology to simultaneous detection of human leucocyte antigen and human platelet antigen antibodies

Abstract: In this study, we developed a rapid, simple and reliable method for the simultaneous analysis of HLA and HPA antibodies. ICFA can also be used as an alternative to the lymphocyte cytotoxicity test for HLA cross-matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…For such an occurrence, instead of opting not to use CB for the transplantation, it would be beneficial for transplant centers to have access to confirmative tests for antibodies. A test method that targets antigens naturally expressed on the cell surface, such as immunocomplex capture fluorescence analysis 30 or a lymphocyte indirect immunofluorescence test, 31 or alternative crossmatch tests with HLA-typed cells could be helpful in clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…For such an occurrence, instead of opting not to use CB for the transplantation, it would be beneficial for transplant centers to have access to confirmative tests for antibodies. A test method that targets antigens naturally expressed on the cell surface, such as immunocomplex capture fluorescence analysis 30 or a lymphocyte indirect immunofluorescence test, 31 or alternative crossmatch tests with HLA-typed cells could be helpful in clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…HPA-1a alloantibodies are responsible for various syndromes in immune-mediated thrombocytopenia. Although a wide range of assays and techniques have been established (Stafford et al, 2008;von dem Borne et al, 1978;Campbell et al, 2007;Meyer et al, 2006a,b;Bakchoul et al, 2007;Fujiwara et al, 2009;Wautier, 2000;Thibaut et al, 2012;Chong et al, 2011;Quiel et al, 2012), the MAIPA is still considered the gold standard for the detection of HPA-1a alloantibodies. However, the sensitivity of many of these assays has been questioned , and interlaboratory variation has been observed in the detection of HPA-specific alloantibodies Sachs et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The odyssey towards HPA-1a alloantibody detection based on immobilization of platelet antigens with monoclonal antibodies (MoAbs) in the assay known as monoclonal antibody-specific immobilization of platelet antigens assay (MAIPA) was first described by Kiefel et al (1987). Since then, dramatic efforts and progress have been made towards establishing alternative assays for HPA-1a alloantibody detection (Stafford et al, 2008;von dem Borne et al, 1978;Campbell et al, 2007;Meyer et al, 2006a,b;Bakchoul et al, 2007;Fujiwara et al, 2009;Wautier, 2000;Thibaut et al, 2012;Chong et al, 2011;Quiel et al, 2012). However, such assays are hampered by the limited availability of MoAbs and suitable platelet donors.…”
Section: Introductionmentioning
confidence: 97%
“…Typically, without any detectable assay cross-reactivity or interference, multiple proteins can be simultaneously quantified within a single sample. It has been widely reported that the ELISA microarray is an efficient tool for measuring the levels of up to 50 proteins with excellent sensitive (∼1 pg/ml), dynamic range (∼3 logs), and low coefficients of varia- [93][94][95][96][97][98][99][100][101] Nitrocellulose on a chip Bind to antibodies in a noncovalent, irreversible manner…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the amount of the targeted PTM on the captured antigens will be measured by this approach. (Colours are visible in the online version of the article; http://dx.doi.org/10.3233/CBM-2009-0140) tion between replicate measurements (5-20%) in small sample volumes (5-20 µl) [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%